2002
DOI: 10.1055/s-2002-19717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Ischemic Preconditioning on Blood-Flow Response in the Epigastric Pedicled Rat Flap

Abstract: Research in the field of microvascular surgery has shown that ischemic preconditioning (repeated brief episodes of feeding artery occlusions followed by reperfusion) improves flap survival. The authors used a custom-designed clamping method and laser Doppler flowmetry to investigate changes in blood flow (BF) responses, either with acute ischemic preconditioning or without it. The animal model used was the partially elevated epigastric flap of adult Sprague-Dawley rats. In the preconditioned group (n=12), the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Stress conditioning is known to advance viability of tissues subjected to ischemia and reperfusion (10,35,36). In line with previous reports, we could confirm the upregulation of HSP32 by heat shock and cooling preconditioning, respectively (10,11,24).…”
Section: Discussionsupporting
confidence: 91%
“…Stress conditioning is known to advance viability of tissues subjected to ischemia and reperfusion (10,35,36). In line with previous reports, we could confirm the upregulation of HSP32 by heat shock and cooling preconditioning, respectively (10,11,24).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that conditioning of endangered flap tissue by ischaemic preconditioning, induction of delay or heat‐shock priming augments nutritional blood supply and improves tissue viability5, 6, 16. A variety of mechanisms have been proposed to augment the blood supply, including closure of shunts17, increase in vascularization18 and improvement in capillary blood flow19.…”
Section: Discussionmentioning
confidence: 99%
“…In an experimental study that used LDFM to investigate blood-flow variation within rat epigastric flaps in acute ischemia and femoral occlusion, Kinnunen et al 34,35 reported that perfusion increases significantly following clamp release (P Ͻ 0.001). In our study, the main reason for the significant perfusion difference is probably the vasospasm that results from the 30-minute clamp application.…”
Section: Discussionmentioning
confidence: 99%